Utilization of Iron (Stainless Steel) Waste for Making Prussian Blue Pigment - Esa Nur Shohih; Cornelius Satria Yudha; Himmah Sekar Eka Ayu Gustiana; Dian Rama Pradifta; Ilmi Utari Simatupang; Kristina Dewi Maharani; Muftiyasfu Tahshilus Sa’adah (Stannum : Jurnal Sains dan Terapan Kimia, 2024)
The increasing use of household materials made of stainless steel also causes more metal waste to be produced. Stainless waste is considered dangerous because it contains several heavy metal compounds such as Ci, Pb, Ni, Fe, and others, so it is necessary to treat stainless waste. Stainless slag and stainless dust can be processed into products with high selling value such as pigments or dyes. In this research, Prussian Blue pigment was synthesized from Fe waste obtained from iron fiber waste. Apart from knowing the yield of the Prussian Blue synthesis, the effect of adding TiO2 on the intensity of the resulting color was observed. This study used a hydrometallurgical method using acid leaching to produce Prussian blue color pigments. The Prussian blue pigment conversion value produced in experiment 1 was 79.63%, experiment 2 was 80.36%, experiment 3 was 83.63%, and experiment 4 was 82.40%. The yield value of Prussian blue pigment in experiment 1 was 1.230 gram Prussian blue/gram iron, experiment 2 was 1.142 gram Prussian blue/gram iron, experiment 3 was 1.305 gram prussian blue/gram iron, and experiment 4 was 1.807 gram prussian blue/gram iron. Overall this method can process waste iron (stainless steel) into Prussian blue color pigment.